Identifikasi Sedimen Urine pada Penduduk yang Mengkonsumsi Air Sumur di Desa Besole Kecamatan Besuki Kabupaten Tulungagung - Chalies Diah Pratiwi; Eka Puspitasari (Borneo Journal of Medical Laboratory Technology, 2019)
Drinking water that is consumed should be clean and healthy. To avoid illness and disruption of bodily functions such as kidney function, liver, brain, teeth, and even mental disorders. Some people in Besole village still use dug well water as a source of drinking water. The geographical state of the town of Besole, Tulungagung district, is a mountainous area of marble containing lime which allows for mineral content, main calcium in the drinking water of residents. This study aims to determine the identification of urine sediments in residents who consume well water in Besole Village, Besuki District, Tulungagung Regency in 2018. This type of research is descriptive non-analytic, by determining the percentage of urine sediments that consume well water through an examination at the Pathology Laboratory STIKes Hutama Abdi Husada Tulungagung. The number of samples is 30 people, with simple random sampling technique. Based on the research conducted found the results of abnormal urine sediment percentage, ie, 6.7% leukocytes, 3.3% erythrocytes, 16.7% epithelium, 30% calcium oxalate and 3.3% bacteria. Water containing lime should be boiled, precipitated and filtered before consumption.